1998
DOI: 10.3168/jds.s0022-0302(98)75825-4
|View full text |Cite
|
Sign up to set email alerts
|

Using Milk Urea Nitrogen to Predict Nitrogen Excretion and Utilization Efficiency in Lactating Dairy Cows

Abstract: Because animal agriculture has been identified as a major source of nonpoint N pollution, ways to reduce the excretion of N by production animals must be examined. The objective of this research was to develop and evaluate a mathematical model that integrates milk urea N to predict excretion, intake, and utilization efficiency of N in lactating dairy cows. Three separate digestibility and N balance studies (10 diets, 40 cows, and 70 observations) were used to develop the model, and 19 independent studies (93 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
288
5
57

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(375 citation statements)
references
References 36 publications
25
288
5
57
Order By: Relevance
“…Wood et al (2003) reported similar trends in MUN with stage of lactation. Jonker et al (1998) found a decrease of MUN with advancing DIM from around the second month onward, leading to a curve for MUN similar to that for milk yield. Jorritsma et al (2003) hypothesized that MUN might be increased under a negative energy balance, suggesting a peak in MUN during early lactation like Jonker et al (1998).…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Wood et al (2003) reported similar trends in MUN with stage of lactation. Jonker et al (1998) found a decrease of MUN with advancing DIM from around the second month onward, leading to a curve for MUN similar to that for milk yield. Jorritsma et al (2003) hypothesized that MUN might be increased under a negative energy balance, suggesting a peak in MUN during early lactation like Jonker et al (1998).…”
Section: Resultsmentioning
confidence: 56%
“…Jonker et al (1998) found a decrease of MUN with advancing DIM from around the second month onward, leading to a curve for MUN similar to that for milk yield. Jorritsma et al (2003) hypothesized that MUN might be increased under a negative energy balance, suggesting a peak in MUN during early lactation like Jonker et al (1998). Broderick and Clayton (1997) also found a positive relationship between MUN and DIM, but the data analyzed by Spicer et al (2000) indicated that MUN increased during the first 3 weeks of lactation, then remained steady for the remainder of the lactation.…”
Section: Resultsmentioning
confidence: 56%
“…The concentration of rumen ammonia is an indicator of protein degradation, dietary nitrogen utilization, and microbial growth Russell, 2002). Similarly, the blood urea concentration is a sensitive and immediate indicator of the animal protein metabolism, whereas the milk urea-N is a better indicator than blood urea for evaluating the metabolism of N compounds in the rumen because homeostatic mechanisms do not regulate milk urea-N, a variable less affected by postprandial variations (Jonker et al, 1998). Considering the amino acid requirement of lactating animals and dietary amino acid supply, it is possible that RUP sources can promote better productive responses when combined with forages such as sugarcane or elephant grass silage.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction Milk urea nitrogen (MUN; mg N/dL) is positively related to excretion of urinary urea N (UUN; g/d) (Burgos et al, 2007) and total N (UN; g/d) (Jonker et al, 1998;Bannink and Hindle, 2003) and can therefore be used as an indicator of N-utilization. However, Bannink and Hindle (2003) observed in a meta-analysis on 9 studies that the prediction of UN was substantially improved (R 2 increased from 0.79 to 0.84) when one study, in which the effect of salt intake on urine production was tested, was omitted.…”
Section: Methodsmentioning
confidence: 99%